Innovations in daily commuting - what types of solutions are competitive? European case study. - Wolny - Kucińska, Ada; Dudzińska, Małgorzata; Dawidowicz, Agnieszka; Gross, Marta (Bulletin of Geography. Socio-economic Series, 2024)
Innovations drive dynamic changes in daily commuting especially in functional urban areas (FUAs), where transport systems are developed. Innovative solutions are being tested in FUAs, and they not only pose an alternative to conventional transport systems, but can also revolutionize daily commuting in cities. The main aim was to classify the innovation drivers identified in literature and to determine their impact on travel behaviour (TB) in FUAs with a use of expert survey. The following research hypothesis was examined: the level of innovation utilization in daily commuting and its impact on TB is similar in countries with similar levels of economic development. The survey results were processed to (1) create a ranking of innovations in TB in European OECD countries and (2) group countries based on similarity in prioritizing innovations influencing TB, using Ward hierarchical clustering method. As a result, innovative factors were comprehensively identified and classified in six categories.